A modular minicell configuration for mass customisation manufacturing. (19th March 2007) - Badurdeen, Fazleena; Masel, Dale
Mass customisation aims at providing products and services to meet individual customer needs at near mass production efficiency. Successful mass customisation requires a manufacturing system that is highly flexible to adapt to customer needs, has low lead times, and enables customisation at a low cost. Developing a manufacturing system to achieve all these requirements, which seemingly is a paradox, is one of the major challenges to successful mass customisation. This paper presents an approach to configure the manufacturing system as a collection of minicells, dedicated to producing option families, to which products can be routed depending on the customisation needs of each customer.